USE OF DISTANCE SCOMING DATA IN LAND RESOURCE MONITORING - Siddikov Rasuljon Uktamovich; Ergasheva Marjona Otabek kizi (Web of Journals Publishing, 2025)
This article analyzes the possibilities and practical experience of using remote sensing (RS) technologies in land resource monitoring. Near-real-time monitoring of soil, vegetation cover, water resources, and land degradation is carried out through the RS. International and domestic research has been studied, and existing shortcomings in this area in Uzbekistan have been identified - personnel potential, obsolescence of technical equipment, and limitations of advanced analysis methods. It was also noted that the availability of free satellite data and open scientific platforms creates great opportunities for the further development of RS technologies in our country. As a result, it has been scientifically substantiated that improving the land resource monitoring system based on remote sensing will serve to increase environmental sustainability and agricultural efficiency.
Keywords: Distance sensing, land resource monitoring, soil fertility, satellite data, NDVI, environmental monitoring, Uzbekistan, agro-monitoring.